Die agro-ökologische Trockengrenze. Neu-Definition und Dynamik der Trockengrenze des Regenfeldbaus in den zentralen Great Plains von Nord-Amerika - Späth, Hans-Joachim (ERDKUNDE, 1980)
In all semi-arid regions agricultural land use is stimulating the process of desertification. Therefore, a new approach to dryland use must be found. It should be an approach both ecologically sound and practically feasable. Such an approach mainly deals with the search for a new definition of the dry boundary of non-irrigated agriculture. Falkner’s (1938) definition of the dry boundary of non irrigated agriculture is based on mean values of temperature and precipitation. It does not take into consideration actual land use patterns and problems. Furthermore it cannot be used as a planning tool in resource management, in soil and moisture conservation, or in reclamation programs for moisture-deficit zones damaged by wind erosion. Taking reclamation and conservation aspects as well as longterm ecological stability into consideration the dry boundary is adjacent to places where soil erosion can just be effectively controlled. The complete absence of destructive soil erosion is the principal criterion of the new ecological definition of the dry boundary of non-irrigated agriculture. According to this definition this new boundary will be called “agro-ecological dry boundary. The relationships,soil /soil moisture’, available moisture / grain yield’, grain yield / straw yield’, ,minimum straw requirement / wind erosion control’, tillage / remaining residue rate’ are integrated into the equation for determining the location of the agro-ecological dry boundary. The equation reads Fopt= ((100*Remin)/(b*d*(100-Ti))) – ((a+b*c)/(b*d) where Fopt= optimized moisture supply; Remin = minimum residue rate for effective erosion control required at planting time; Ti = residue loss due to tillage between harvest and planting time in %> of prell-tillage residue rate a = Y-intercept and b = slope of local grain/straw yield regression equation; c = Y-intercept and d = slope of local available moisture/grain yield-regression equation. By means of this formula the agro-ecological dry boundary can be localized for the various soils, cropping systems, and years (= moisture supply conditions). Due to its character this formula can be used as a guide for planning local and regional land use patterns and practices. There is no regional limitation to its applicability.